ETIKA MAKAN DAN MINUM DALAM PRESPEKTIF ISLAM DAN PENGARUHNYA BAGI KESEHATAN - Purwanto, Aulia Nur Fatikha Rakhmah; Hajar Nisaul Halimah; Muslikhah Al Fikriyatul Insan; Aprilia Putri Utami (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the role of eating etiquette in preventing obesity and gastritis and the challenges of implementing it among adolescents in the modern era. The increasing obesity rate in Indonesia is often caused by unhealthy eating patterns, including high consumption of fast food. This study uses a qualitative method with literature analysis to explore the relationship between eating etiquette from an Islamic perspective and health. The results show that implementing the principles of mindful eating and balanced nutrition can help prevent obesity and gastritis. In addition, the practice of eating etiquette recommended in Islam, such as choosing halal and thayyib foods, washing hands before eating, and reciting prayers, contribute to physical and mental health. The discussion in this study highlights the negative impacts of unhealthy eating patterns and the importance of educating the public about the teachings of the Prophet Muhammad in eating etiquette. The conclusion of this study confirms that the implementation of eating etiquette not only plays a role in preventing disease, but also contributes to improving the overall quality of life. This study is expected to fill the gap in the literature regarding the positive impacts of eating etiquette practices on health and provide insight into the development of nutrition education based on Islamic values